Film-Forming and Metabolic Antitranspirants Reduce Potato Drought Stress and Tuber Physiological Disorders - Oluwatoyin Favour Olu-Olusegun; Aidan Farrell; James Monaghan; Peter Kettlewell (Agronomy)
Potatoes are highly sensitive to drought, particularly during tuber initiation. This study aimed to evaluate the effectiveness of film-forming (Vapor Gard [VG]) and metabolic (abscisic acid [ABA]) antitranspirants in mitigating drought stress and reducing tuber physiological disorders in four potato varieties. Two experiments examined the effects of VG and ABA antitranspirants on drought-stressed potato plants of four varieties (Challenger, Markies, Nectar, and Russet Burbank) grown in pots in a polytunnel (semi-controlled environment). Experiment 1 imposed severe drought by withholding irrigation until 70% of the available water content was depleted (reaching 15–17% volumetric water content within ~15 days), while Experiment 2 featured gradual drought stress from tuber initiation, with the soil volumetric water content declining to <10% over 30 days. Antitranspirants were applied at the start of the tuber initiation and two weeks later to assess their impact on the soil volumetric water content, stomatal conductance, relative water content, yield, and tuber physiological disorders. Drought significantly reduced the soil and plant water status, tuber yield, and quality across both experiments, with more severe effects observed in Experiment 1. VG and ABA had repeatable effects in both experiments and in all varieties, reducing water stress by preventing a large reduction in the relative water content during the tuber initiation and bulking stages. Both antitranspirants improved the tuber appearance by reducing the tuber skin disorder of russeting in the susceptible Challenger variety in both experiments, with VG being more effective than ABA. Beneficial reductions in the effects of drought from antitranspirants were also recorded in the volumetric water content, stomatal conductance, yield, and jelly end rot but not consistently in all varieties and in both experiments. The results show that antitranspirants have the potential to minimise water stress in droughted potatoes and subsequently reduce the physiological disorder of russeting and improve the tuber appearance of the Challenger variety.